Improving Runway Capacity from Operation Management View Point by Evaluating Critical Factors and The Mitigation Plan at Soekarno-Hatta International Airport Jakarta - Wasid, Muhamad; Firman, Aries F (The Indonesian Journal of Business Administration, 2015)
Abstract - Economic prosperity brings greater demand for travel. The increasing affordability of air travel has opened up new destinations and possibilities. The availability of sufficient airport capacity is an important constraint on future growth. However, even at current levels of use, many airports in the world are becoming increasingly congested as they attempt to cope with rising passenger numbers. In some cases, the capacity of terminals, apron and runways is at, or near, saturation point, SHIA also faces the same situation. The data collected in this research is primary data that obtained from interviewing of ten (10) key personnel from several professions and work unit in SHIA and secondary data obtained from internal AP II and literature review on documents that related with this research. The data then will be analyzed using fishbone diagram and research construct analysis to find the critical factors. The first step that can be done to solve the problems regarding runway capacity improvements is by conducting identification about the important factors that could improve runway capacity at SHIA airport. There are 16 important factors that affecting the determination of runway capacity improvement at SHIA. The most influential factors are ATC Separation Requirement, Rapid Exit Taxiway (RET) Number and Position, and New 3rd Runway.Â Keywords : Airport, Runway Capacity, Congestion, Delays, Critical Factor.Â